False positive cardiac troponin elevation due to heterophile antibodies: more common than we recognise?. (16th July 2010) - Zaidi, Abbas; Cowell, Richard
Abstract : A 53-year-old woman was admitted with non-exertional chest pain and elevated cardiac troponin I (cTnI) without dynamic changes of ischaemia on the ECG. She had recently undergone coronary angiography which had shown normal coronary vessels. Repeat angiography on this admission was again unremarkable. Samples of blood were sent for analysis using different troponin assays and demonstrated chronic basal elevation of cTnI while simultaneous assay for troponin T (cTnT) remained normal. Subsequent testing revealed the presence of heterophile antibodies interfering with the troponin I assay leading to a false positive result.